A Legal Review of Wills that Harm Heirs - Haerul, Digma Wahyuni; Aswari, Aan (Constitutional Law Review, 2023)
The purpose of the research is to analyze the distribution of inheritance according to the provisions of Islamic law and civil law and to find out and analyze the legal protection for heirs who are canceled due to the existence of a will. The research used is normative legal research. This research is conducted by analyzing the rules regarding wills that harm heirs. The results of this study indicate that the teachings of Islam in relation to inheritance, Islamic law itself has provided arrangements regarding the elements, conditions and pillars, as well as the qualifications of heirs concerning the rights and obligations in terms of giving and receiving inheritance to heirs sourced from verses of the Koran, nashnash Prophetic traditions, ijma' and ijtihad. And in positive law the distribution of inheritance has been regulated in the Civil Code which discusses the people who are entitled to be heirs, and if the heirs feel sued because of the granting of a will, this has been regulated in inheritance law regarding Legitime Portie, where the heirs have absolute rights to their inheritance so that the heirs who submit can file a lawsuit for their Legitime Portie that has been violated. Recommendations It is hoped that there will be a renewal of the will so that the heirs get the inheritance according to the law and no heirs are harmed by the granting of the will to non-heirs